Participation in question: issue or counterpoint of the representation in the democratic theory? - Laisner, Regina (FCL-UNESP Laboratório Editorial, 2009)
In order to try to approach the participation as a theme, this article goes inside the democratic theory, from its classical ideals to the most contemporary issues, exploring significances and understanding how this mechanism is related to the representation idea. The objective is to recover the connections between participation and representation in the democratic theory, different from a predominant view of democracy that tries to push them away from each other, proposing, at the end, a participation perspective which presents itself not as a replacement strategy, but as complement of the representative democracy, in the sense of improvement.